Fundamentals of enterprise risk management : how top companies assess risk, manage exposures, and seize opportunities - Hampton, John J., 1942- (American Management Association, 2009)
After the devastation experienced by AIG, Bear Stearns, Lehman Brothers, and other financial institutions, the need for effective, comprehensive enterprise risk management (ERM) systems has never been more stark or immediate.